Consequences of diverse evolutionary processes on american genetic gradients of modern humans. (December 2018) - Branco, Catarina; Velasco, Miguel; Benguigui, Macarena; Currat, Mathias; Ray, Nicolas; Arenas, Miguel
Abstract European genetic gradients of modern humans were initially interpreted as a consequence of the demic diffusion of expanding Neolithic farmers. However, recent studies showed that these gradients may also be influenced by other evolutionary processes such as population admixture or range contractions. Genetic gradients were observed in the Americas, although their specific evolutionary causes were not investigated. Here we extended the approach used to study genetic gradients in Europe to analyze the influence of diverse evolutionary scenarios on American genetic gradients. Using extensive computer simulations, we evaluated the impact of (i) admixture between expansion waves of modern humans, (ii) the presence of ice-sheets during the last glacial maximum (LGM) and (iii) long-distance dispersal (LDD) events, on the genetic gradients (detected by principal component analysis) of the entire continent, North America and South America. The specific simulation of North and South America showed that genetic gradients are usually orthogonal to the direction of range expansions—either expansions from Bering or posterior re-expansions to recolonize northern regions after ice sheets melting—and we suggest that they result fromallele surfing processes. Conversely, our results on the entire continent show a northwest-southeast gradient obtained with any scenario, which we interpreted as a consequence of isolation by distance along the long length of the continent. These findings suggest that distinct genetic gradients can be detected at different regions of the Americas and that subcontinent regions present gradients more sensible to evolutionary and environmental factors (such as LDD and the LGM) than the whole continent.